2003
DOI: 10.1242/dev.00676
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Bdnf and TrkB signalling in the postnatal cochlea leads to a spatial reshaping of innervation along the tonotopic axis and hearing loss

Abstract: Members of the neurotrophin gene family and their high-affinity Trk receptors control innervation of the cochlea during embryonic development. Lack of neurotrophin signalling in the cochlea has been well documented for early postnatal animals, resulting in a loss of cochlear sensory neurones and a region-specific reduction of target innervation along the tonotopic axis. However, how reduced neurotrophin signalling affects the innervation of the mature cochlea is currently unknown. Here, we have analysed the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 50 publications
10
118
0
1
Order By: Relevance
“…8), occupying the same region as the SK2 channel (17), suggests a vital role of the BK current in the efferent inhibitory control. Whatever the function of BK on OHCs level, the similarity of basal to apical declining gradients of BK expression (present study) and the gradient of efferents (26) and presumptively afferent type II (22) indicates that BK channels play a role in maintaining those OHCs that receive efferent inhibitory feedback from the brain.…”
Section: Bk␣ Gene Deletion Leads To Hearing Loss Associated With Ohcsupporting
confidence: 53%
See 2 more Smart Citations
“…8), occupying the same region as the SK2 channel (17), suggests a vital role of the BK current in the efferent inhibitory control. Whatever the function of BK on OHCs level, the similarity of basal to apical declining gradients of BK expression (present study) and the gradient of efferents (26) and presumptively afferent type II (22) indicates that BK channels play a role in maintaining those OHCs that receive efferent inhibitory feedback from the brain.…”
Section: Bk␣ Gene Deletion Leads To Hearing Loss Associated With Ohcsupporting
confidence: 53%
“…Hearing Measurements. Anesthesia of animals, measurements of auditory brainstem responses (ABR), and distortion products of the otoacoustic emissions (DPOAE) were performed as described (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia of animals, measurements of auditory brainstem responses (ABRs), and the cubic distortion product of the otoacoustic emissions (DPOAEs) were performed as described previously (Knipper et al, 2000;Schimmang et al, 2003;Carnicero et al, 2004). Briefly, ABR thresholds were determined with click (100 s) or pure tone stimuli (2-45 kHz).…”
Section: Methodsmentioning
confidence: 99%
“…In late post-natal stages of these mutant mice, a lack of afferent innervation in the apical part of the cochlea has been shown, while the basal portion was unaffected but in older stages, the opposite was true. The reshaping of innervation was probably regulated by autocrine signaling between neurotrophins and their receptors in cochlear neurons (Schimmang, et al 2003). Embryonic inner ear developmental in chick (Hallbook and Fritzsch 1997) and murines (Ernfors et al 1994) has also revealed the biological significance of BDNF expression for both afferent and efferent fiber innervation.…”
Section: Introductionmentioning
confidence: 99%